2019
DOI: 10.4103/idoj.idoj_372_18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Possible Role of FOXP3 Gene (rs3761548) Polymorphism in Psoriasis Vulgaris Susceptibility and Pathogenesis: Egyptian Study

Abstract: Background: Psoriasis is an autoimmune-related chronic inflammatory skin disorder. Psoriasis vulgaris (PV) is the most common form of psoriasis. T regulatory cells (Tregs) are typically considered inhibitors of autoimmune responses. FOXP3 is a master control transcription factor for development and function of Tregs. FOXP3 gene polymorphism changes FOXP3 protein function and quantity leading to Tregs dysfunction that subsequently may be related to PV pathogenesis. Objective: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The forkhead box P3 (FOXP3) is a key transcription factor in the development and function of Tregs [ 17 ]. Previous studies have demonstrated a genetic association between the FOXP3 gene and PsO [ 61 , 62 ]. FOXP3 gene polymorphism may change FOXP3 protein activity, leading to the dysfunction of Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…The forkhead box P3 (FOXP3) is a key transcription factor in the development and function of Tregs [ 17 ]. Previous studies have demonstrated a genetic association between the FOXP3 gene and PsO [ 61 , 62 ]. FOXP3 gene polymorphism may change FOXP3 protein activity, leading to the dysfunction of Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the FOXP3 gene, located on the X chromosome, encodes a protein from the fork-winged helix family of transcription factors which plays an essential role in modulating regulatory T cells and can act as a transcriptional repressor or activator depending on its interactions with other transcription factors, histones, acetylases, and deacetylases [ 51 , 52 ]. Alterations in FOXP3 (rs3761548; G>C/T/A) can potentiate the inflammatory cascade in psoriasis and consequently not respond to and/or provoke AEs due to MTX treatment [ 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%